High temperature Si–Ge alloy towards thermoelectric applications: A comprehensive review. (November 2021) - Basu, R.; Singh, A.
Abstract: Silicon–Germanium is an excellent and well-proven alloy with wide application in the transistor technology and space industries because of its meritorious features such as easy to form both n- and p-type depending on the dopant, environment friendliness, highly abundant material on earth's crust, high mechanical strength etc. This review article highlights the status, potential, and challenges associated with thermoelectric applications. In spite of the fact that Si–Ge exhibits a complex phase diagram due to the wide separation between the solidus and liquidus line, solid-state synthesis could overcome the difficulties associated with the homogeneity and is an epitome to achieve single-phase alloy. Moreover, the beauty of the method is that the yield of the product is very high. This review article also encompasses the strategies involved to reduce the thermal conductivity of the alloy which is otherwise essential to have high figure-of-merit ( zT ). It also highlights the importance of bulk nanostructuring, which still embraces the title of highest ever reported zT of both n- and p-type bulk Si–Ge alloy. Towards the end, the review opens up a new avenue for exploring methods to reduce the internal resistance of the Si–Ge unicouple and fabrication of DC-DC booster circuit so that the demand for higher voltage can be realized. Graphical abstract: Image 1 Highlights: Superiority of the Si–Ge alloy in contrast to elemental Si in thermoelectric and transistor technology was reviewed. All the solid-state synthesis methods were discussed in detail in order to obtain homogeneous alloy. Strategies to reduce the thermal conductivity and enhance the zT of the alloy were discussed. Fabrication of unicouple and the technological challenges involved at various electrical contacts were reviewed. Towards the end, article highlights the global status of the thermoelectric modules and its future prospect in market size.